2016
DOI: 10.1016/j.surg.2015.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Integrating “big data” into surgical practice

Abstract: openAccessArticle: Falsecover date: 2016-02-01pii: S0039-6060(15)00805-3Harvest Date: 2016-01-06 13:08:15issueName:Page Range: 371-371href scidir: http://www.sciencedirect.com/science/article/pii/S0039606015008053pubType: Surgical Research Revie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…This novel method of data management will have an incredible impact on patient care, diagnosis and treatment which will result in a reduction in patient morbidity and mortality as well as population outbreaks and in nosocomial infections within hospitals (Forkan et al, 2017). Big Data offers opportunities in clinical medicine including: (1) patient involvement is increased by creating accessible and understandable data, (2) personalized medicine is translated into healthcare and (3) new knowledge is generated and disseminated (Mathias et al, 2016). Table 3 (Nydegger et al, 2016) shows advantages, disadvantages/drawbacks and measures (for drawbacks) of big data in EHRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel method of data management will have an incredible impact on patient care, diagnosis and treatment which will result in a reduction in patient morbidity and mortality as well as population outbreaks and in nosocomial infections within hospitals (Forkan et al, 2017). Big Data offers opportunities in clinical medicine including: (1) patient involvement is increased by creating accessible and understandable data, (2) personalized medicine is translated into healthcare and (3) new knowledge is generated and disseminated (Mathias et al, 2016). Table 3 (Nydegger et al, 2016) shows advantages, disadvantages/drawbacks and measures (for drawbacks) of big data in EHRs.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic medicine incorporates genomics-based diagnostics into practice. The entire human genomic and exomic sequence (i.e., whole-genome sequencing), is now available and can be used for less expensive and rapid individual analysis (Mathias et al, 2016). Table 4 (Wooden et al, 2017) shows some publicly available big data resources and their description.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to studies of sepsis in adults, there is active research examining both clinical and research measurements applicable to a pediatric population. One current tool which may be available in the near future is the implementation of biomarkers or ‘-omic’ (including genomics, transcriptomics, proteomics, and metabolomics) information that may provide diagnostic and prognostic capability early in the course of sepsis (14). This information may also help stratify this heterogeneous patient population into subgroups for more tailored therapeutic approaches (15).…”
Section: Defining Sepsismentioning
confidence: 99%
“…All one needs to do is watch television and see the advertisements from large information warehouses, like IBM, General Electric, Google and Microsoft. As this information database grows and the tools to extract biological information from this data improve, we will see the advent of personalized medicine where treatment is tailor-made to the individuals unique physiology (14). Although this technology seems far off, there are already genomic markers that can identify which patients will benefit from corticosteroid therapies (15).…”
Section: Managementmentioning
confidence: 99%
“…BG is a key structural polysaccharide of the cell wall of most fungi and the authors have revealed that it can be used as a marker of gastrointestinal leakage and sepsis, even during/after bacterial infections (10). As clinicians are moving towards precision medicine (11), this type of biomarker will prove vital as scientists tailor therapy only to those individuals that require intervention.…”
mentioning
confidence: 99%